Cholelithiasis in obese adolescents treated at an outpatient clinic - Marília M. de A. Nunes; Carla C.M. Medeiros; Luciana R. Silva (Jornal de Pediatria (Versão em Português), 2014)
Objective: to describe the frequency and the factors associated with cholelithiasis in obese adolescents. Methods: this was a cross-sectional descriptive study performed with the adolescents between 10 and 19 years of age treated at the Child and Adolescent Obesity Outpatient Clinic from May to December of 2011. Obesity was defined as body mass index (BMI) > P97, and overweight as BMI > P85, for age and gender, according to the 2007 World Health Organization reference. A questionnaire concerning the presence of signs and symptoms, such as abdominal pain, nausea, vomiting, and intolerance to fat, was administered. Patients were asked about how many kilograms they had lost and in how much time. Laboratory parameters were: triglycerides, total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels. Cholelithiasis and hepatic steatosis were diagnosed by ultrasonography. Results: cholelithiasis was diagnosed in 6.1% (4/66) of the obese adolescents, most of whom were female (3/4); hepatic steatosis was identified in 21.2% (14/66). Intolerance to dietary fat was reported by all patients with cholelithiasis (4/4) and by 17.7% (11/62) of the group without cholelithiasis (p = 0.001). The average weight loss was 6.0 ± 2.9 kg in the patients with cholelithiasis and 3.2 ± 4.8 kg in the group without cholelithiasis (p = 0.04). However, there was no difference between the two groups regarding the time of weight loss (p = 0.11). Conclusions: cholelithiasis and hepatic steatosis are frequent among obese adolescents and should be investigated systematically in the presence or absence of symptoms.